2022
DOI: 10.31730/osf.io/4v2p7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pedagogical integration of technology as an enhancement to teaching and learning in Gauteng public schools

Abstract: The study explores how Information Communication Technology (ICT) can be integrated in the daily school activities of Gauteng public schools from views of educators, Heads of Departments (HODs) and subject advisors. The aim of the study was to explore the degree of the ICT integration within Gauteng public schools, the challenges impeding the optimum utilisation of ICT towards curriculum delivery and enabling conditions for ICT rollout in education transformation. Therefore, the study's objectives were to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, the findings showed that female educators are not fully prepared to utilise ICT in teaching. The irony though was that the study found out that most ICT Champions in Gauteng schools were female (Ntsobi, 2021).…”
Section: Influence Of Gender On Educators 'Preparedness To Use Ict In...mentioning
confidence: 97%
See 1 more Smart Citation
“…Also, the findings showed that female educators are not fully prepared to utilise ICT in teaching. The irony though was that the study found out that most ICT Champions in Gauteng schools were female (Ntsobi, 2021).…”
Section: Influence Of Gender On Educators 'Preparedness To Use Ict In...mentioning
confidence: 97%
“…Gauteng Province has been at the forefront of digital transformation in schools, prioritising public schools in general and township schools in particular (Ntsobi, 2021). Therefore, as stated by Bladergroen, Chigona, Bytheway, Cox, Dumas, and van Zyl (2012:107), the implementation of educational innovation through the integration of ICT in teaching and learning is deemed as critical and pivotal in terms of economic advancement and people development in Gauteng Province.…”
Section: Introductionmentioning
confidence: 99%